Gestión administrativa y financiera del Comercial Joselito del Cantón Baba periodo 2022 - Cabello Garaicoa, Fiorella Mayddu (2023)
Comercial Joselito is a company dedicated to the purchase and sale of essential products, it is located in the Baba canton of the province of Los Ríos; enterprise that arose in order to generate socioeconomic well-being to its owners and to satisfy the needs of the population, however, in recent years the institutionality of the commercial in the administrative and financial field presents various shortcomings, being necessary to prevent, for this reason the The objective of this research is to evaluate the administrative and financial management period 2022; the methodology is based on the use of descriptive, inductive, deductive methods through the application of strategic quantitative and qualitative diagnostic analysis; whose results assessed the situational state of the company, concluding that it is necessary to maintain and retain customers, for which reason strategies related to customer service and service are recommended, which lead to loyalty in an environment of quality and safety.